Genetic Background but Not Intestinal Microbiota After Co-Housing Determines Hyperoxaluria-Related Nephrocalcinosis in Common Inbred Mouse Strains - Ma, Qiuyue; Grigorescu, Melissa; Schreiber, Adrian; Kettritz, Ralph; Lindenmeyer, Maja; Anders, Hans-Joachim; Steiger, Stefanie (Frontiers in Immunology, 2021)
Calcium oxalate (CaOx) crystal formation, aggregation and growth is a common cause of kidney stone disease and nephrocalcinosis-related chronic kidney disease (CKD). Genetically modified mouse strains are frequently used as an experimental tool in this context but observed phenotypes may also relate to the genetic background or intestinal microbiota. We hypothesized that the genetic background or intestinal microbiota of mice determine CaOx crystal deposition and thus the outcome of nephrocalcinosis. Indeed, Casp1-/-, Cybb-/- or Casp1-/-/Cybb-/- knockout mice on a 129/C57BL/6J (B6J) background that were fed an oxalate-rich diet for 14 days did neither encounter intrarenal CaOx crystal deposits nor nephrocalcinosis-related CKD. To test our assumption, we fed C57BL/6N (B6N), 129, B6J and Balb/c mice an oxalate-rich diet for 14 days. Only B6N mice displayed CaOx crystal deposits and developed CKD associated with tubular injury, inflammation and interstitial fibrosis. Intrarenal mRNA expression profiling of 64 known nephrocalcinosis-related genes revealed that healthy B6N mice had lower mRNA levels of uromodulin (Umod) compared to the other three strains. Feeding an oxalate-rich diet caused an increase in uromodulin protein expression and CaOx crystal deposition in the kidney as well as in urinary uromodulin excretion in B6N mice but not 129, B6J and Balb/c mice. However, backcrossing 129 mice on a B6N background resulted in a gradual increase in CaOx crystal deposits from F2 to F7, of which all B6N/129 mice from the 7th generation developed CaOx-related nephropathy similar to B6N mice. Co-housing experiments tested for a putative role of the intestinal microbiota but B6N co-housed with 129 mice or B6N/129 (3rd and 6th generation) mice did not affect nephrocalcinosis. In summary, genetic background but not the intestinal microbiome account for strain-specific crystal formation and, the levels of uromodulin secretion may contribute to this phenomenon. Our results imply that only littermate controls of the identical genetic background strain are appropriate when performing knockout mouse studies in this context, while co-housing is optional.